Involving Men in Reproductive and Fertility Issues : Insights from Punjab - Kamran, Iram; Khan, Mumraiz; Tasneem, Zeba (World Bank, Washington, DC, 2014)
Pakistan's slackening in its fertility transition is a cause of concern internationally, as well as within the country. This study has a twofold aim of exploring couples' dynamics during decision processes regarding fertility intentions and practices along with community perceptions of male-focused interventions and men's suggestions for future intervention strategies. The findings are based on three data sources. The primary data source is a 2013 qualitative study in four districts of Punjab province. The second data source is secondary analysis of the baseline and end line surveys of the Family Advancement for Life and Health (FALAH 2007-2012) project. The third data source is the Pakistan Demographic Health Survey (PDHS) 1990-1991 and 2006-2007, which were used to assess trends over two decades. The 2013 qualitative study was in four districts of Punjab, namely Jhelum, Bahawalpur, D.G. Khan, and Okara. The first three were FALAH districts in which interventions were tested, while the fourth was chosen as a control district. A total of 12 focus group discussions were conducted with men, and in-depth interviews were conducted with 26 couples in these districts. Data from 2,649 men and 638 couples from the FALAH baseline and end line surveys were analyzed to assess the impact of FALAH male-directed interventions on fertility intentions and behavior. This study seeks to explore the decision-making process of couples in the move from intentions to fertility behavior. It also examines the readiness of men to be involved in family planning (FP) programs through different male-centered interventions. In-depth interviews (IDIs) with couples are especially direct in gauging spousal perception of the partner's FP approval or disapproval. The study focuses on urban and semi-urban areas of Punjab province and can be used, at least indicatively, for interregional and temporal analyses within the Pakistani context.